Balancing Acts: (Meta)theatricality and violence. (19th May 2019) - Willis, Emma
Abstract : This article examines how theatricality, specifically metatheatricality, functions in the depiction of perpetrators of violence and considers this from an ethical perspective. Performances that dwell on the ideologies and behaviours of perpetrators of violence are difficult to stage and present a range of ethical problems, including whether it is appropriate to grant the privilege of 'presence' to such figures, the risk of reiterating violent ideology, the risk of occluding the experiences of the victims and sensitivity to survivors of violence. These ethical problems in turn generate a set of aesthetic problems. This article focuses on two case studies where metatheatrical devices are used as a response to the challenges outlined above: Manifesto 2083 (2012), a solo performance about mass-murderer Anders Behring Breivik by Danish theatre-makers Christian Lollike, Olaf Højgaard and Tanja Diers; and Joshua Oppenheimer's documentary about Indonesian government death squads of the 1960s, The Act of Killing (2012). While metatheatricality may at first glance seem to negate theatricality through pointing to the constructedness of theatrical illusion, I draw from Samuel Weber's explanation of theatricality, in particular his notion of 'linked separation, ' to suggest that metatheatricality, in fact, constitutes an intensification of theatricality. Moreover, I propose that the concept of 'linked separation' provides an effective critical lens through which to scrutinize the ethical dimensions of the uses of metatheatricality as a response to violence.